'Holland and we were bot one in our cause': The Covenanters' 'Dutch' Reception and Impact. (December 2020) - Mijers, Esther
Abstract : This article examines aspects of the reception of the covenanters and their cause in the Dutch republic from the start of the civil wars to the return of the Restoration exiles almost five decades later. It begins by looking at the foundations of the Scottish-Dutch religious relationship before addressing the Dutch reaction to the rise of the covenanters, the arrival of Scottish exiles in the Dutch republic and the formation of several Scottish-Dutch religious networks, with particular attention paid to publishing and translation activities. The article concludes with reflection on the reception and impact of covenanter ideas as interpreted by their Dutch supporters.